2019
DOI: 10.3390/s19183857
|View full text |Cite
|
Sign up to set email alerts
|

Portable Skin Analyzers with Simultaneous Measurements of Transepidermal Water Loss, Skin Conductance and Skin Hardness

Abstract: Simultaneous measurement of skin physiological and physical properties are important for the diagnosis of skin diseases and monitoring of human performance, since it provides more comprehensive understanding on the skin conditions. Current skin analysis devices, however, require each of probes and unique protocols for the measurement of individual skin properties, resulting in inconvenience and increase of measurement uncertainty. This paper presents a pen-type skin analyzing device capable tomeasure three key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(44 reference statements)
0
13
0
1
Order By: Relevance
“…The research group developed a series of portable devices for multimodal skin analysis (e.g., skin hardness and conductance) in a single probe based on the novel idea of the automatic actuated chamber. [ 155 , 156 ] In the future, such devices for multimodal skin analysis are expected to be wearable, similar to the watch‐type SLMDs they developed.…”
Section: Advances Of Wearable Sweat Loss Measuring Devicesmentioning
confidence: 99%
“…The research group developed a series of portable devices for multimodal skin analysis (e.g., skin hardness and conductance) in a single probe based on the novel idea of the automatic actuated chamber. [ 155 , 156 ] In the future, such devices for multimodal skin analysis are expected to be wearable, similar to the watch‐type SLMDs they developed.…”
Section: Advances Of Wearable Sweat Loss Measuring Devicesmentioning
confidence: 99%
“…Mapping skin in terms of its properties has a long history and has received increasing attention in the last two decades. This in part reflects the evolution of the measuring devices, some of which have become available only in recent times [10][11][12]. Research about regional differences of the skin thickness dates back to the early 1970s with the works of Holbrook et al [13] and has generated a number of relevant studies since [4,[14][15][16].…”
Section: Related Researchmentioning
confidence: 99%
“…One of the recent studies demonstrated a skin probe that enabled three different biomarker measurements (Figure 7c ). [ 215 ] The skin probe included a truncated hollow cone probe [ 216 ] housing a force sensor, a thermometer, and a conductance sensor with the capability to measure a sweat rate. The narrow end and closed hollow structure characteristics enabled adequate skin hardness and sweat rate detections, enabling one to measure three different physical biomarkers simultaneously.…”
Section: Practical Challenges On Wearable Human Heath and Performance...mentioning
confidence: 99%